Split bolus dual-energy CT urography after urine dilution: a one-stop shop for detection and characterisation of urolithiasis. Issue 8 (August 2020) - Manoharan, D.; Sharma, S.; Das, C.J.; Kumar, R.; Kumar, P.
Abstract : AIM: To determine the diagnostic performance of split-bolus dual-energy computed tomography (CT) urography (SBDECTU) in the detection and characterisation of urolithiasis. MATERIALS AND METHODS: This single-centre Institute Ethics Committee (IEC)-approved prospective study was conducted from April 2014 to November 2015. One hundred and thirty consenting adults with microscopic haematuria underwent dual-energy true non-enhanced CT (DETNE) of the whole abdomen followed by a SBDECTU. The SBDECTU protocol consisted of synchronous nephrogram–urogram acquisition following urine dilution by oral hydration and normal saline injection. Calculi were detected and characterised using virtual non-enhanced (VNE) images derived from SBDECT were compared with DETNE (the reference standard). The subjective image quality and radiation dose were compared. RESULTS: Twenty-six participants had one or more calculi (total 129 calculi) detected on DETNE CT. The sensitivity and specificity of VNE on a per-patient basis were 100%. Of the 129 calculi, 118 were detected on VNE, with a sensitivity of 91.47% and an accuracy of 91.47%. Of the calculi, 83.9% (99/118) could be characterised on SBDECTU images. On VNE images, complete iodine subtraction was seen in 73.1% (19/26). By omitting DETNE CT, the mean dose–length product of 537.6±152.9 mGy and volume CT dose index of 10.9±2.9 mGycm 2 could have been saved. CONCLUSION: SBDECTU has high diagnostic accuracy in the detection and characterisation of clinically significant urinary calculi at potentially half the radiation dose. Highlights: Split bolus DECT urography following urine dilution had 100% accuracy per-patient. It had 91.47% accuracy on per-calculi basis. 83.9% of calculi were correctly characterized. Average dose reduction of 537.6 mGy radiation is possible.